Proposed new design scheme of outlet for Sarakraf Sdn Bhd Lot 231, Off Jalan Ampang dalam Bandaraya Kuala Lumpur / Tengku Arbaiyah Tengku Abdul Rahman - Tengku Abdul Rahman, Tengku Arbaiyah (Faculty of Architecture, Planning and Surveying, 2006)
The main aim of this project is to introduce to the visitors can sample Sarawak’s unique blend of art, handicrafts, music, culture and food all under one roof and To give student some flavour of the demand, pressures and excitement that comes from managing the design interface with client, consumer and some indication of the specific roles responsibilities involved in retail design and the range of knowledge, skill and judgment needed to fulfill a design role in a retail. A series of interview and observation had been conducted in collecting relevant data and information. A set of data had been collected for the references such as magazines, internet and books. In conclusion, this outlet is not limited for tourists but also focuses on every society. It will help people appreciate our culture especially Sarawak Culture and bring them to higher level. The same time, it will encourage most of the ethnic people to show their talent.